THE RELEVANCE OF BRAIN NATRIURETIC PEPTIDES INVESTIGATION IN VARIOUS CARDIOVASCULAR DISEASES - Kotaska, Karel; Popelova, Jana; Tiserova, Marie; Telekes, Peter; Vrzanova, Marie; Bronsky, Jiri; Halacova, Milada; Kukacka, Jiri; Prusa, Richard (Biomedical papers, 2006)
Background: Brain natriuretic peptides are relevant markers of heart impairment.Aim: We investigated the relevance of investiging brain natriuretic peptides (NT-proBNP, BNP) in monitoring different types of cardiovascular disease (chronic heart failure due to coronary artery disease, cardiomyopathy, acquired valve disease, congenital heart diseases).Methods: The NT-proBNP assay (Roche) was performed on 280 patients (mean age 49 years; range 20-89 years) and 48 healthy controls (mean age 43 years; range 13-65 years) and BNP assay (Bayer Shionoria) was performed in a subgroup of 42 patients (mean age 50 years; range 20-79 years). Patients were divided into four groups characterized by severity of heart failure according to the New York Heart Association classification.Results: NT-proBNP concentrations differed in patients with cardiovascular diseases from controls (median 371 ng/l versus 41.5 ng/l, p < 0.0001). The cut off value of NT-proBNP determined in 280 patients with cardiovascular diseases was at 130 ng/l (AUC-area under curve = 0.93; sensitivity 98 %; specificity 79 %). Comparison of NT-proBNP and BNP values in patients showed significant correlation (r = 0.93; p < 0.0001). NT-proBNP showed significant differences between groups.Conclusions: Measurement of brain natriuretic peptides is useful and relevant in various types of heart diseases including congenital.
Keywords: Brain natriuretic peptides/BNP/NT-proBNP/Cardiovascular diseases/NYHA classification